A segregation analysis of Malaysia's International Trade Pattern / Abdul Aziz Lai Mohd Fikri Lai - Mohd Fikri Lai, Abdul Aziz Lai (2018)
The current decade waves a challenging period for the global economy due to several factors such as the plummeting of global crude oil prices, heightened geopolitical conflicts in various parts of the world and slow post-crisis recovery by developing and under developed countries (United Nations Department of Economic and Social Affairs, 2015). As one of the major exporters of crude oil, Malaysia has been greatly affected by the world market destabilization as witnessed in the drastic drop of total trade performance by 19.23% within 2 years - 2014 to 2016. Likewise, unfortunate events such as the missing of flight MH 370, the tragedy of MH 17, Sulu invasion in Sabah and major floods in some parts of the country are also believed to have caused a stir in the economy. Therefore, it is crucial for Malaysia to restructure its movement of trade to improve its Trading Across Borders performance. This thesis attempts to extend the epistemology of international trade in Malaysia by adopting the technique of partner segregation effect. In this technique, trading partners which consists of 132 countries were segregated based on region, income and development category. Apart from the segregation technique, this study also employed the classic Gravity Theory of Trade (GTT) in constructing the empirical model which incorporates the Cross-Sectional analysis, Static Panel analysis and Generalized Method of Moments. In general, empirical findings from this study shows that Malaysia's trade pattern differs according to groups of trading partners. For instance, Malaysia's trade with developed and high income nation tend to follow Linder's theory while Malaysia's trade with least developed and low income countries tend to follow the Heckscher-Ohlin theory. Additionally, the volume of trade with rich countries tend to be higher compared to the poorer countries. In relation to regional segregation, the overall findings suggest that Malaysia tend to trade more with countries in the Asian region compared to other regions. As a whole, this thesis discovered that the utilization of partner segregation technique and robust estimation technique in trade studies could yield more comprehensive and insightful findings. The discovery in the current work contributes to the body of knowledge of Malaysia international trade, thus allowing policy makers to improve trade policies and consequently sustain the country's economic growth.